Translation Strategies for Islamic Terms Used by English Teachers in the English Classroom - Randa, Alyaa Hilmianti; Imani, Anugrah; Sulaeman, Dedi; Rohaedi, Tedi; Kurniawati, Nia (STAIN Sultan Abdurrahman Kepulauan Riau, 2024)
This study aims to explore the translation strategies for Islamic terms used by English teachers. The study focuses on preservation, addition, globalization, and localization strategies used by English teachers in an Islamic school in Bekasi. It delves into the importance of accurate translation to convey the essence of Islamic terms, highlighting the reason for strategies that English teachers used. This study utilized a qualitative research approach to investigate the translation strategies employed by English teachers in Islamic schools. The research involved primary data collection through observation and interviews with English teachers at Quba Islamic School in Bekasi. Two English teachers, one for the lower and one for the upper levels, were selected as research subjects. The result found that preservation is the most common strategy for teachers when teaching students Islamic terms. However, teachers use fewer addition strategies. Teachers also use globalization of Islamic terms, which involves a global or universal perspective in teaching Islamic terms. Meanwhile, teachers do not use localization strategies in the English classroom. Additionally, these studies underscore the significance of teachers shaping students' understanding of Islamic terms through various strategies.